PENDAPAT PARA FUQOHA DAN MAJELIS ULAMA INDONESIA (MUI) TENTANG FILOSOFI DAN HIKMAH LARANGAN PERNIKAHAN BEDA AGAMA SERTA DAMPAKNYA - Farida, Annikmah (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2016)
Marriage as in islamic law is not civil case alone. But ties saint to mistaqan ghalizhan is a firm covenant and strong. For that marriage be maintained well, so what be the goal marriage namely the formation of family couple mawaddah wa mercy can be achieved. According to the indonesian ulemas council one of a barrier the formation of the purpose of marriage as above, is marriage different religion .But phenomena marriage different religion occurring dimasyarakat actually of an increasing and as if becomes regular issues. Remembering how the importance of problems marriage different religion widespread in indonesia.Hence, the indonesian ulema menguluarkan fatwa on prohibition of different religion marriage.Focus of study this writing is: (1) Think fuqoha and the indonesian ulema about a philosophy and wisdom ban different religious marriage? (2). How the impact of marriage different way?